Innovation and the sharing economy : employment, human capital, and the AI revolution - Kumar, Pawan (Routledge, 2025)
"This book is a novel exploration of the complex interplay between modern work structures, ar-tificial intelligence (AI), and economic sustainability. Through meticulously researched insights and real-world examples, this book unravels the in-tricate dynamics shaping the sharing and gig economies, offering a comprehensive analysis of their implications for the future of work. Key features of this book include a deep dive into the theoretical foundations of AI, the sharing economy, and gig economy, complemented by practi-cal case studies illustrating their real-world applications. Readers will gain valuable insights into how these economic models influence labour markets, technological advancements, govern-ance frameworks, and societal well-being. By examining the opportunities and challenges pre-sented by the sharing and gig economies, this book equips readers with the knowledge to navi-gate and shape the evolving landscape of work. This edited collection caters to a diverse audience, including academics, technologists, policy-makers, students across various disciplines, and professionals interested in the future of work and economic development. Its interdisciplinary approach makes it an invaluable resource for those seeking a deeper understanding of the complexities surrounding AI, the sharing economy, and the gig economy. Whether you're a researcher, entrepreneur, or policymaker, this book provides essential insights into the transformative forces shaping the global economy"-- Provided by publisher.
Keywords: Labor supply -- Effect of technological innovations on.; Artificial intelligence -- Economic aspects.; Gig economy.; Human capital.; elektronické knihy; electronic books